Multiple Intelligences in the English Learning Context - Freitas, Amanda Cristina de (2022)
This paper aimed to present the results of our research on the challenges of planning English language classes in elementary school through the analysis of didactic activities proposed for a 2nd grade Elementary class in a private school. This is a descriptive documentary research with a mixed approach (quantitative and qualitative) that sought to investigate whether didactic activities include aspects related to the theory of multiple intelligences (linguistic, musical, logical-mathematical, spatial, bodily-kinesthetic, interpersonal, intrapersonal, and naturalist) proposed by Howard Gardner in 1983 (Gardner, 1994). From the initial analysis of lesson plans, the results show the predominance of activities that focus exclusively on logical-mathematical and linguistic intelligences.